Facilitating Transactions and Lawful Availability of Works of Authorship: The U.S. Perspective - Kasunic, Robert J. (The Columbia Journal of Law & the Arts, 2018)
As Associate Register of Copyrights and Director of Registration Policy and Practice at the United States Copyright Office, a significant part of my role is to be an advocate for formalities within the limits of the Berne Convention. I realize that many view registration, recordation, and other formalities as obstacles to authors. However, such formalities need not be impediments, but rather may offer valuable benefits to authors, owners, and the overall copyright ecosystem without unduly burdening creators.